GAMBARAN POLA TERAPI KANKER PAYUDARA DENGAN KEMOTERAPI PASIEN JAMINAN KESEHATAN NASIONAL DI RSUP Dr. SARDJITO YOGYAKARTA - Anggra Olgabella Esthetica Aragon; Fitria Dyah Ayu Surya Negara (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2015)
Background: Breast canceri ncidencse until now still become the highest type of cancer in Indonesia. The terapy can performed by the several ways, one of this is by chemotherapy. Objectives:This study aimed to describe the pattern of treatment and the type of chemotherapy drug used in breast cancer with chemotherapy inpatients National Health Insurance (JKN) at Dr Dr. Sardjito. Methods:Research is an observational study with cross sectional study design and data retrospective methods of data collection through the medical records of patients. The total study sample was 126 patients with 205 cases that met the inclusion criteria, the most patient age range is at 46-55 years (44.4% of total patients). The hingest severity level of patients is severity level I (76.1%). Result: Chemotherapy drugs used in each patient varies according to the condition and severity of disease. Chemotherapy drugs also cause adverst events during treatment. However, only a small proportion of patients who experienced adverse events (nausea and vomiting 2.4% and 0.5% decreased appetite). It because before being given the chemotherapy drug, the patient was given premedication with dexametason, ondansetron, ranitidine and diphenhydramine injection. Conclusion A chemotherapy drug that is most widely used is a combination of doxorubicin and cyclophosphamide in 65 cases.